Revenant modernisms and the recurrence of literary history - Schultz, Matthew (International Journal of English Studies, 2017)
This essay suggests that literary production post-postmodernism has not progressed to something new, but rather has returned to quintessentially modernist anxieties and modes of expression––especially renewed faith in grand narratives. The argument draws upon and coalesces two theoretical texts to help identify what I term ‘revenant modernism’ as a “symbolic space” (Flatley, 2008: 32) where a sort of “secular re-enchantment” (Landy & Saler, 2009: 2) remains possible: Jonathan Flatley’s Affective mapping: Melancholia and the politics of modernism (2008) and The re-enchantment of the world: Secular magic in a rational age (2009) by Joshua Landy and Michael Saler. I then examine two recent novels––Will Self’s Umbrella (2012) and Eimear McBride’s A girl is a half-formed thing (2014)––as evidence of this return. Along the way, I tie both of these novels back to their stated modernist influence (James Joyce’s Ulysses [1993]) in order to show how Self and McBride’s fiction borrows from Joyce’s particular brand of postcolonial modernism.